Open rotunda, Frere Temple - Ghosh, Ayan (2023)
The 35-foot-tall Frere Temple was designed by William Tracey, an engineer of the Public Works Department who also designed the Victoria and Albert Museum (Dr. Bhau Daji Lad Museum) and the triple-arched gateway at the entrance to the Garden. The temple cost ₹ 42,000, which was raised through public subscription. The central part of the rotunda is open to the sky.